Estimation of power generation capacities of a wind farms installed in windy sites in Algerian high plateaus. (April 2017) - Abdeslame, Djamila; Kasbadji Merzouk, Nachida; Mekhtoub, Said; Abbas, Mohamed; Dehmas, Mokrane
Abstract: The data of the wind data (speed and direction) measured over one period 10 consecutive years, of four sites located in the Algerian high plateaus, were used to determine the regional atlases of wind speed and the power densities of the areas. The results allowed the estimate of the optimal production of wind farm composed by four wind turbine adding up a rated capacity of 8 MW. The Weibull parameters, the mean wind speed and the power density according to different values of heights and roughness factors were calculated for the considered sites. The effects on the annual electrical output production in function of the RIX factor that determines the best site of the wind farm in the area and the wake effects were analyzed. The results show that the two regions, Tiaret and M'Sila are more profitable and are adapted for wind farms installation comparing with the others. Highlights: Using Wasp software, we produce the Wind climate at 10 m a.g.l. of four sites located in Algerian high plateaus. Microclimate Atlas of wind speeds and wind resources were estimated and compared. The AEP is estimated assuming that the farm is composed by four 2 MW wind turbines installed at 67 m a.g.l. We optimize the distance between neighbouring turbines to increase the AEP.